Development of Ethnosciene Reels of Ketapang Malay Tribe as Supplementary Learning Resources on Hydrocarbon Compounds - Laila Fitri; Raudhatul Fadhillah; Dini Hadiarti (Jurnal Penelitian Pendidikan IPA, 2025)
The habit of the Malay community in using natural materials as fuel can be integrated into chemistry teaching materials in schools. The aim of this research is to assess the validity and practicality of reels as a learning resource and to develop reels based on the ethnoscience of the Ketapang Malay tribe. The research development model used is the Three Stages Research and Development (TSRD) model, which consists of three steps: planning, development, and dissemination. Data collection techniques involve indirect communication using validation sheets and response instruments. The subjects of the research are students from SMA N 1 Sungai Laur. The results of the study indicate that the ethnoscience-based reels of the Malay tribe are valid and practical, with validity and practicality scores of 96.3% and 90.30%, respectively. The reels can be used as an independent, practical, and engaging learning resource that is relevant to students. Therefore, the validity and practicality results of the development of ethnoscience-based reels are expected to serve as an innovative and contextual alternative media for chemistry education in schools.